Histone Acetyltransferase SlGCN5 Regulates Shoot Meristem and Flower Development in Solanum lycopersicum - Hawar, Amangul; Xiong, Shiqi; Yang, Zhen; Sun, Bo (Frontiers in Plant Science, 2022)
The histone acetyltransferase (HAT) general control non-repressed protein 5 (GCN5) plays important roles in plant development via epigenetic regulation of its target genes. However, the role of GCN5 in tomato, especially in the regulation of tomato shoot meristem and flower development, has not been well-understood. In this study, we found that silencing of Solanum lycopersicum GCN5 (SlGCN5, Solyc10g045400.1.1) by virus-induced gene silencing (VIGS) and RNA interference (RNAi) resulted in the loss of shoot apical dominance, reduced shoot apical meristem (SAM) size, and dwarf and bushy plant phenotype. Besides, we occasionally observed extra carpelloid stamens and carpels fused with stamens at the late stages of flower development. Through gene expression analysis, we noticed that SlGCN5 could enhance SlWUS transcript levels in both SAM and floral meristem (FM). Similar to the known function of GCN5 in Arabidopsis, we demonstrated that SIGCN5 may form a HAT unit with S. lycopersicum alteration/deficiency in activation 2a (SlADA2a) and SlADA2b proteins in tomato. Therefore, our results provide insights in the SlGCN5-mediated regulation of SAM maintenance and floral development in tomato.